ZWITTERMICIN RESISTANCE GENE, ZmaR FROM A MARINE BACILLUS SP. DMB 8 ISOLATED FROM SOUTH EAST COAST OF INDIA - ALAKNANDA SARKAR,; KIRAGANDUR MANJUNATH, (International Journal of Pharma and Bio Sciences, 2015)
Nonribosomal peptide synthetase (NRPS) adenylation (A) domain genes were investigated by polymerase chain reaction for 41 bacteria with antibacterial activity isolated from south eastern coast of India. 8 bacteria were found to contain NRPS genes, all of which showed antimicrobial activity against multiple human bacterial pathogens including gram positive and gram negative bacteria. One of the isolates, Bacillus sp. DMB 8 exhibited effective antibacterial activities. Partial sequence analysis of 16S rRNA gene revealed that this isolate is similar to Bacillus pseudomycoides (99%). But its colony morphology and Scaning electron microscopy shows remarkable difference from Bacillus pseudomycoides. Furthermore, a gene designated ZmaR was detected by means of specific amplification of DNA fragment approximately 1037 bp. Sequence analysis revealed that it had highest homology with Bacillus cereus zwittermicin A resistance (ZmaR) gene (U57065.1). The combined molecular technique and bioassay strategy will be useful to obtain marine bacteria with the potential to synthesize bioactive compounds.